2022
DOI: 10.3389/fgene.2022.829384
|View full text |Cite
|
Sign up to set email alerts
|

Novel Immune-Related Ferroptosis Signature in Esophageal Cancer: An Informatics Exploration of Biological Processes Related to the TMEM161B-AS1/hsa-miR-27a-3p/GCH1 Regulatory Network

Abstract: Background: Considering the role of immunity and ferroptosis in the invasion, proliferation and treatment of cancer, it is of interest to construct a model of prognostic-related differential expressed immune-related ferroptosis genes (PR-DE-IRFeGs), and explore the ferroptosis-related biological processes in esophageal cancer (ESCA).Methods: Four ESCA datasets were used to identify three PR-DE-IRFeGs for constructing the prognostic model. Validation of our model was based on analyses of internal and external d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…We used TCGA ESCA database with external ESCA dataset GSE53624 to assess and verify the predictive ability of our prognostic model [53,54]. The Clinical and survival information of the whole set was derived from the TCGA dataset, and the external dataset GSE53624 was obtained from the GEO database through the GEO query R package.…”
Section: Validation Of Predictive Modelmentioning
confidence: 99%
“…We used TCGA ESCA database with external ESCA dataset GSE53624 to assess and verify the predictive ability of our prognostic model [53,54]. The Clinical and survival information of the whole set was derived from the TCGA dataset, and the external dataset GSE53624 was obtained from the GEO database through the GEO query R package.…”
Section: Validation Of Predictive Modelmentioning
confidence: 99%
“…In the present study, SRR was found to have positive correlations with TMB and MSI in UCEC. Furthermore, the correlations between SRR and some immune inhibitors, such as PDCD1 and CTLA4, which have been reported to enhance the immune responses, were striking ( Fan et al, 2021b ; Lu et al, 2022 ). Immune checkpoint expression also differed between the SRR-high and SRR-low expression groups.…”
Section: Discussionmentioning
confidence: 98%
“…We discovered that the IC50 of doxorubicin, docetaxel, and paclitaxel was higher in the SRR-low expression group than in the SRR-high expression group, implying that patients with SRR-high expression were more sensitive to these drugs. Because chemotherapy drugs can have serious adverse effects, it is vital to screen people who are sensitive to them so that adverse reactions are minimized ( Fan et al, 2021b ; Lu et al, 2022 ). SRR expression could also be used as a biomarker to screen patients with UCEC for chemotherapy, according to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…668 samples from TCGA cohort were randomly matched to the training set ( n = 334) and test set ( n = 334) on average. Lasso regression analysis can screen out highly relevant PR-DE-IRGs from the training set, thereby minimizing the risk of overfitting the screening features, and achieving the purpose of accurately predicting the patients’ prognosis ( Lu et al, 2022 ). The optimal penalty parameter ( λ ) obtained by the minimum 10-fold cross validation was used to determine five PR-DE-IRGs and corresponding coefficients for constructing the prognostic model.…”
Section: Methodsmentioning
confidence: 99%